Paternal De Novo Variant of TAOK1 in a Fetus With Structural Brain Abnormalities - Yu, Lihua; Yang, Chaoxiang; Shang, Ning; Ding, Hongke; Zhu, Juan; Zhu, Yuanyuan; Tan, Haowen; Zhang, Yan (Frontiers in Genetics, 2022)
A dilated lateral ventricle is a relatively common finding on prenatal ultrasound, and the causes are complex. We aimed to explore the etiology of a fetus with a dilated lateral ventricle. Trio whole-exome sequencing was performed to detect causative variants. A de novo variant of TAOK1 (NM_020791.2: c.227A>G) was detected in the proband and evaluated for potential functional impacts using a variety of prediction tools. Droplet digital polymerase chain reaction was used to exclude the parental mosaicism and to verify the phasing of the de novo variant. Based on peripheral blood analysis, the parents did not exhibit mosaicism at this site, and the de novo variant was paternally derived. Here, we describe a fetus with a de novo likely pathogenic variant of TAOK1 who had a dilated lateral ventricle and a series of particular phenotypes. This case expands the clinical spectrum of TAOK1-associated disorders. We propose a method for solving genetic disorders in which the responsible genes have not yet gone through ClinGen curation, particularly for prenatal cases.